2000
DOI: 10.1177/109980040000200203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Autonomic Nervous System Indices Based on Abdominal Pain Reports in Women with Irritable Bowel Syndrome

Abstract: Abdominal pain is an important symptom in irritable bowel syndrome (IBS), but patients report typical pain intensities ranging from mild to very severe. In a sample of women, the authors sought to determine whether measures of systemic autonomic activity are related to self-reported pain intensity and the occurrence of pain in the postprandial period. One hundred and six women with IBS and 41 controls completed bowel symptom and psychological distress questionnaires and wore 24-h Holter electrocardiogram monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
6
44
0
Order By: Relevance
“…Because autonomic dysfunction has been linked to many of the common features of FM including pain (Burr, Heitkemper, Jarrett, & Cain, 2000;Schurmann et al, 2000), chronic fatigue (Naschitz et al, 2000), sleep disturbances (Wiklund et al, 2000), depression (Agelink et al, 2001;Rechlin, 1994;Yeragani, Balon, Pohl, & Ramesh, 1995) generalized anxiety disorder (Thayer, Friedman, & Borkovec, 1996), and panic disorder Asmundson & Stein, 1994;Rechlin, Weis, Spitzer, & Kaschka, 1994), autonomic dysfunction has been the target of a number of investigations (Bou-Holaigah, Rowe, Kan, & Calkins, 1995;Clauw, Radulovic, Heshmat, & Barbey, 1996;Cohen et al, 2001;Elam, Johansson, Wallin, 1992;Kelemen, Lang, Balint, Trocsanyi, & Muller, 1998;Martinez-Lavin et al, 1997;Martinez-Lavin, Hermosillo, Rosas, & Soto, 1998;Qiao, Vaeroy, & Morkrid, 1991). Preliminary evidence supports the hypothesis that autonomic dysfunction, characterized by a high baseline state of sympathetic arousal and decreased parasympathetic activity resulting in a blunted sympathetic response to stressors, is a potential pathogenic mechanism in FM (Clauw & Chrousos, 1997;Martinez-Lavin, 2004).…”
Section: Fibromyalgia and Autonomic Dysfunctionmentioning
confidence: 99%
“…Because autonomic dysfunction has been linked to many of the common features of FM including pain (Burr, Heitkemper, Jarrett, & Cain, 2000;Schurmann et al, 2000), chronic fatigue (Naschitz et al, 2000), sleep disturbances (Wiklund et al, 2000), depression (Agelink et al, 2001;Rechlin, 1994;Yeragani, Balon, Pohl, & Ramesh, 1995) generalized anxiety disorder (Thayer, Friedman, & Borkovec, 1996), and panic disorder Asmundson & Stein, 1994;Rechlin, Weis, Spitzer, & Kaschka, 1994), autonomic dysfunction has been the target of a number of investigations (Bou-Holaigah, Rowe, Kan, & Calkins, 1995;Clauw, Radulovic, Heshmat, & Barbey, 1996;Cohen et al, 2001;Elam, Johansson, Wallin, 1992;Kelemen, Lang, Balint, Trocsanyi, & Muller, 1998;Martinez-Lavin et al, 1997;Martinez-Lavin, Hermosillo, Rosas, & Soto, 1998;Qiao, Vaeroy, & Morkrid, 1991). Preliminary evidence supports the hypothesis that autonomic dysfunction, characterized by a high baseline state of sympathetic arousal and decreased parasympathetic activity resulting in a blunted sympathetic response to stressors, is a potential pathogenic mechanism in FM (Clauw & Chrousos, 1997;Martinez-Lavin, 2004).…”
Section: Fibromyalgia and Autonomic Dysfunctionmentioning
confidence: 99%
“…Indicators of ANS dysfunction, that is, low vagal tone and greater sympathetic drive, are more prevalent in individuals with IBS compared to healthy controls. 9 It is not possible to determine whether the ANS imbalance contributes directly to the pathophysiology or is the outcome of IBS (eg, result of chronic stress and suppression of vagal input). However, it has been shown that physical exercise, which increases HRV, does have positive benefit for IBS patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, current evidence support altered HRV and autonomic functions when predominant bowel patterns (14,17), pain severity (18), sleep patterns (16), and presence of anxiety or depression (19) are taken into account. A recent meta-analysis comparing 392 IBS patients with 263 healthy control subjects revealed lower HF band and higher LF/ HF ratio in patients with IBS.…”
Section: Discussionmentioning
confidence: 99%
“…The association of altered HRV and IBS has long been sought. Although, several observational studies has focused on impaired HRV in patients with IBS, the results of these studies are controversial; some found no difference (14-16) whereas others revealed differences in HRV when patient characteristics like predominant bowel patterns (14,17), pain severity (18), sleep patterns (16), and presence of anxiety or depression (19) were taken into account. To date, the association of HRV and atherosclerosis markers in the setting of IBS has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%